Boosting sustainable hydrogen production via water splitting and urea oxidation using spinel hollow-sphere nano catalysts - Hsin‐Yu Lin; Dhanapal Vasu; Chun-Han Tsang; Chiajen Hsu; Gopi Prashanth; Te‐Wei Chiu; Naratip Vittayakorn (Sustainable materials and technologies, 2025)
In this study, spinel MgCo 2 O 4 materials were synthesized using three different techniques: freeze-drying, solid-state, and hydrothermal methods, to evaluate their structural, morphological, and electrocatalytic properties. Comprehensive characterization techniques including XRD, Raman spectroscopy, FT-IR, FESEM, HRTEM, and XPS confirmed the successful formation of phase-pure MgCo 2 O 4 with varied morphologies. Among the synthesized materials, the freeze-dried sample exhibited a well-defined hollow-sphere structure, providing abundant electroactive sites and superior electron/mass transport pathways. This morphology contributed to outstanding electrocatalytic performance. For the oxygen evolution reaction (OER), the hollow-sphere MgCo 2 O 4 catalyst demonstrated a low overpotential of 430 mV at 10 mA cm −2 and a Tafel slope of 190 mV dec −1 . In addition, the same catalyst exhibited excellent activity for the urea oxidation reaction (UOR), with a Tafel slope of 95 mV dec −1 and enhanced current density under alkaline conditions. The superior UOR activity, enabled by the lower oxidation potential of urea (∼0.37 V vs. RHE), also highlights its potential for energy-efficient hydrogen production and wastewater treatment. This work establishes a scalable and cost-effective strategy to synthesize high-performance MgCo 2 O 4 hollow-sphere electrocatalysts, paving the way for their application in sustainable energy and environmental technologies. • MgCo₂O₄ electrocatalysts synthesized via freeze-drying, solid-state, and hydrothermal methods. • Freeze-dried sample formed hollow spheres, enhancing surface area and conductivity. • Achieved low overpotential (430 mV) and Tafel slope (190 mV dec −1 ) for OER. • Demonstrated efficient UOR with a Tafel slope of 95 mV dec −1 and high current density. • Dual OER/UOR activity supports low-cost, scalable hydrogen production and wastewater treatment.
Keywords: Electrocatalysts for Energy Conversion; Advanced Photocatalysis Techniques; Catalytic Processes in Materials Science